Environmental Law Regulations and their Enforcement in the Era of Industrial Revolution 4.0 - Indrastuti, Lusia; Putri, Indira Hanaya (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
National Development is the government’s efforts in realizing the development of a just and prosperous society according to the Preambleof the Constitution of 1945. The conditions of economic growth and political stability and environmental law in the Era of IndustrialRevolution 4.0 are increasingly maintained, so the challenges and demands to overcome various problems need to be immediately addressedwell. To continue the aspirations of the nation’s founders, environmental preservation must be carried out properly and in accordance withthe continuity of sustainable development. The manifestation of the implementation of the Law on Environmental Protection andManagement must be prioritized to preserve the environment and create environmental comfort for the wider community. The presentstudy used normative juridical library research by conducting an analysis of applicable laws and regulations as well as legal referencesrelated to the topic of the present study. The results revealed that the role of the state in enforcing environmental law should be done strictlyand performed through educative legal sanctions, and the participation of community members can be practiced well through socializationon increasingly changing regulations.Keywords: Environmental Law, Environmental Sustainability